Epidemiology of overuse and acute injuries among competitive collegiate athletes - Yang, J.; Tibbetts, A. S.; Covassin, T.; Cheng, G.; Nayar, S.; Heiden, E. (Journal of Athletic Training, 2012)
Abstract: Context: Although overuse injuries are gaining attention, epidemiologic studies on overuse injuries in male and female collegiate athletes are lacking. Objective: To report the epidemiology of overuse injuries sustained by collegiate athletes and to compare the rates of overuse and acute injuries. Design: Descriptive epidemiology study. Setting: A National Collegiate Athletic Association Division I university. Patients or Other Participants: A total of 1317 reported injuries sustained by 573 male and female athletes in 16 collegiate sports teams during the 2005-2008 seasons. Main Outcome Measure(s): The injury and athlete-exposure (AE) data were obtained from the Sports Injury Monitoring System. An injury was coded as either overuse or acute based on the nature of injury. Injury rate was calculated as the total number of overuse (or acute) injuries during the study period divided by the total number of AEs during the same period. Results: A total of 386 (29.3%) overuse injuries and 931 (70.7%) acute injuries were reported. The overall injury rate was 63.1 per 10 000 AEs. The rate ratio (RR) of acute versus overuse injuries was 2.34 (95% confidence interval [CI] = 2.05, 2.67). Football had the highest RR (RR = 8.35, 95% CI = 5.38, 12.97), and women's rowing had the lowest (RR = 0.75, 95% CI = 0.51, 1.10). Men had a higher acute injury rate than women (49.8 versus 38.6 per 10 000 AEs). Female athletes had a higher rate of overuse injury than male athletes (24.6 versus 13.2 per 10 000 AEs). More than half of the overuse injuries (50.8%) resulted in no time loss from sport. Conclusions: Additional studies are needed to examine why female athletes are at greater risk for overuse injuries and identify the best practices for prevention and rehabilitation of overuse injuries.